Early-age heat flow and hydration in cementitious composites: numerical modelling based on temperature measurements. Issue 1 (1st January 2022) - Martinelli, E; Pepe, M; Lima, C
Abstract: The heat generated during early age cement hydration causes a semi-adiabatic temperature rise of hardening concrete, while starting to develop its physical and mechanical properties. As a matter of principle, the heat generated by the hardening mixture depends on the cement properties and its hardening conditions like for instance the type of binders, quality of aggregates, water-to-cement ratio and type of formwork. A simple 1D numerical model can be formulated for simulating the evolution in time of this reaction, in order to identify the so called degree of hydration. The present paper proposes a detailed description of a theoretical approach which allow to assess the temperature development occurring in concrete elements at the early-age when the produced mixture is cured in semi-adiabatic boundary conditions. In this numerical procedure, the differential heat equation takes into account the heat that liberates to the environment through the formwork or concrete's surface. This is done by considering the Arrhenius Principle and assuming a pre-defined shape of the adiabatic hydration curve of the concrete mixture. Hence, an indirect identification procedure of the aforementioned adiabatic curve is ideally carried out, as the simulated temperature evolution in semi-adiabatic conditions is brought to match the temperature measurements on a hardening concrete sample. This modelling procedure, enabling various boundary conditions, ranging from semi-adiabatic to isothermal, can be used to calculate the degree of hydration of a real in-situ cast concrete. Specifically, considering the variation of concrete strength class and element size some possible applications are proposed: this represents a simplified approach for the prediction of the temperature time-evolution in the concrete elements at early-age which may be also used as a practical tool for mitigating the risk of premature cracking.